GABA-A receptor modulating steroids in acute and chronic stress; relevance for cognition and dementia? - S.K.S. Bengtsson; T. Bäckström; R. Brinton; R.W. Irwin; M. Johansson; J. Sjöstedt; M.D. Wang (Neurobiology of Stress, 2020)
Cognitive dysfunction, dementia and Alzheimer's disease (AD) are increasing as the population worldwide ages. Therapeutics for these conditions is an unmet need. This review focuses on the role of the positive GABA-A receptor modulating steroid allopregnanolone (APα), it's role in underlying mechanisms for impaired cognition and of AD, and to determine options for therapy of AD. On one hand, APα given intermittently promotes neurogenesis, decreases AD-related pathology and improves cognition. On the other, continuous exposure of APα impairs cognition and deteriorates AD pathology. The disparity between these two outcomes led our groups to analyze the mechanisms underlying the difference. We conclude that the effects of APα depend on administration pattern and that chronic slightly increased APα exposure is harmful to cognitive function and worsens AD pathology whereas single administrations with longer intervals improve cognition and decrease AD pathology. These collaborative assessments provide insights for the therapeutic development of APα and APα antagonists for AD and provide a model for cross laboratory collaborations aimed at generating translatable data for human clinical trials.